Poor response at restaging MRI and high incomplete resection rates of locally advanced mucinous rectal cancer after chemoradiation therapy. (22nd June 2021) - Koëter, Tijmen; Stijns, Rutger C. H.; van Koeverden, Sebastiaan; Hugen, Niek; van der Heijden, Joost Albertus Gerardus; Nederend, Joost; van Zwam, Peter H.; Nagtegaal, Iris D.; Verheij, Marcel; Rutten, Harm J. T.; de Wilt, Johannes H. W.
Abstract: Aim: Mucinous carcinoma is a histological subtype of rectal cancer and has been associated with a poor response to neoadjuvant chemoradiotherapy (CRT). The primary aim of this study was to analyse the response on MRI of mucinous locally advanced rectal cancer (LARC) after CRT compared to regular adenocarcinoma. Method: Patients with LARC (defined as cT4 and/or cN2), who underwent CRT followed by restaging MRI and surgery in two tertiary referral hospitals were retrospectively included in the study. Pre‐ and post‐treatment MRI was reviewed by an experienced abdominal radiologist. Results: A total of 102 patients, of whom 29 were diagnosed with mucinous carcinoma, were included for analysis. At restaging MRI, adenocarcinoma patients demonstrated significantly less clinical involvement of the mesorectal fascia (37% vs. 62%, P  = 0.003) while this was not demonstrated in mucinous carcinoma patients (86% vs. 97%, P  = 0.16). Significant downstaging after CRT in adenocarcinoma patients ( P  = 0.01) was seen while, in mucinous carcinoma patients, no downstaging after CRT ( P  = 0.89) was seen. Pathology revealed significantly higher rates of an involved circumferential resection margin in mucinous carcinoma versus adenocarcinoma patients (27.6% vs. 1.4%; P  < 0.001). After multivariate regression analysis, mucinous carcinoma remained an independent prognostic factor for local recurrence (hazard ratio 3.6; 95% CI 1.1–12.4), although no differences in overall or disease‐free survival were observed. Conclusion: Mucinous rectal carcinoma is associated with a poor clinical response at restaging MRI after CRT, leading to relatively higher rates of involved circumferential resection margins at pathology. In this cohort, mucinous carcinoma seems to be a prognostic factor for increased risk of local recurrence, without an effect on overall survival.